Acquired alexithymia following damage to the anterior insula - Hogeveen, J. (Neuropsychologia, 2016)
Alexithymia is a subclinical condition characterized by impaired awareness of one’s emotional states, which has profound effects on mental health and social interaction. Despite the clinical significance of this condition, the neurocognitive impairment(s) that lead to alexithymia remain unclear. Recent theoretical models suggest that impaired anterior insula (AI) functioning might be involved in alexithymia, but conclusive evidence for this hypothesis is lacking. We measured alexithymia levels in a large sample of brain-injured patients (N=129) and non-brain-injured control participants (N=33), to determine whether alexithymia can be acquired after pronounced damage to the AI. Alexithymia levels were first analyzed as a function of group, with patients separated into four groups based on AI damage: patients with >15% damage to AI, patients with <15% damage to AI, patients with no damage to AI, and healthy controls. An ANOVA revealed that alexithymia levels varied across groups (p=0.009), with >15% AI damage causing higher alexithymia relative to all other groups (all p<0.01). Next, a multiple linear regression model was fit with the degree of damage to AI, the degree of damage to a related region (the anterior cingulate cortex, ACC), and the degree of damage to the whole brain as predictor variables, and alexithymia as the dependent variable. Critically, increased AI damage predicted increased alexithymia after controlling for the other two regressors (ACC damage; total lesion volume). Collectively, our results suggest that pronounced AI damage causes increased levels of alexithymia, providing critical evidence that this region supports emotional awareness.